Perancangan Sistem Informasi Pelaporan KIA Guna Menunjang Program Safe Motherhood Berbasis Elektronik - Zahra, Faridah Fathimatuz; Abdussalaam, Falaah; Sari, Irda (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Health services covering pregnancy, childbirth, postpartum, family planning, and infants and toddlers are included in the scope of the maternal and child health program. Hospital X currently continues to process outpatient data using Microsoft Excel software and has not fully transitioned to electronic patient data. Descriptive qualitative research methodology using a website and phpMyAdmin database is used to produce MCH reports to increase the speed and accuracy of data and create a report format that is suitable for medical staff or hospital management. The stages of requirements analysis, system design, implementation, testing and maintenance are all included in the waterfall development process used for this research software system. Data flow diagrams, flow maps and context diagrams were used in the development of the system design. In summary, this system can minimize data manipulation by assisting the processing of MCH reports, resulting in more accurate and efficient work.